Pengaruh Indeks Saham Syariah Jepang (DJIJP) Dan Indeks Saham Syariah Malaysia (DJMY25D) Terhadap Indeks Saham Syariah Indonesia (ISSI) (Periode Januari Tahun 2016 – Desember Tahun 2020) - Santy Ery Rahayu (At-Thariqah: Jurnal Ekonomi, 2021)
An interesting issue in this study is whether the Japanese Sharia Stock Index (DJIJP) and the Malaysian Sharia Stock Index (DJMY25D) have a partial or simultaneous influence on the Indonesian Sharia Stock Index (ISSI) in the period January 2016 – December 2020 based on the problem. existing and research gaps that have been carried out by previous studies. The purpose of this study was to analyze the effect of the independent variable, namely DJIJP and DJMY25D on the dependent variable, namely ISSI. The research data used is secondary data, namely the closing price index at the end of the month period January 2016 – December 2020. The data analysis method used is multiple linear regression analysis by first testing the classical assumptions. To determine the effect simultaneously, the F test was used and to determine the partial effect, the t test was used. The results of this study indicate that, partially, those that have a positive and significant effect on the ISSI variable are the two DJIJP and DJMY25D variables. Then simultaneously DJIJP and DJMY25D have an influence on ISSI in the period January 2016 – December 2020. The existence of this influence can be influenced by macroeconomic problems as well as technical factors and fundamental factors.